An Intractable Case of Prototheca Keratitis and Chronic Endophthalmitis in Stevens–Johnson Syndrome With Boston Type 1 Keratoprosthesis. Issue 9 (September 2016) - Ng, Jacqueline; Minckler, Don; Walsh, Thomas J.; Farid, Marjan
Abstract : Purpose: To report a case of recalcitrant Prototheca spp. keratitis and endophthalmitis in a patient with Stevens–Johnson syndrome (SJS) and Boston type 1 keratoprosthesis (B1 KPro). Methods: Case report. Results: A 67-year-old female with a history of SJS with chronic severe ocular surface disease in her monocular left eye underwent placement of a B1 KPro. Her course was subsequently complicated by persistent Prototheca spp. keratitis and endophthalmitis requiring ongoing treatment with triazole and polyene antifungal agents and multiple surgical revisions of her keratoprosthesis. Conclusions: Protothecosis is an algal infection that is rarely pathologic in humans, but when present can be difficult to manage. We present the second known case of persistent chronic Prototheca spp. keratitis and endophthalmitis in a patient with long-standing SJS and B1 KPro.